Analisis Parameter Oseanografi Terhadap Hasil Tangkapan Ikan Pelagis Kecil Di Perairan Sinjai - Indrayani Indrayani; Arman Pariakan (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2023)
This study aimed to examine the relationship between seasonal oceanographic conditions (distribution of sea surface temperature, chlorophyll-a concentration, current patterns, and salinity) and catch of small pelagic fish. Analysis was carried out using the survey method and multiple linear regression analysis to determine the relationship between oceanographic factors (temperature, chlorophyll, and salinity) and the catch of small pelagic fish in Sinjai waters. The results showed that the distribution of sea surface temperature in Sinjai waters varied during the study, ranging from 29 to 32°C. Salinity ranged from 28 to 30 ppt, and the chlorophyll-a distribution ranged from 0.15 to 0.3 mg/m3. The three oceanographic factors showed a strong influence (p